2013
DOI: 10.1016/j.jad.2012.07.027
|View full text |Cite
|
Sign up to set email alerts
|

People with bipolar I disorder report avoiding rewarding activities and dampening positive emotion

Abstract: Background Researchers have linked bipolar disorder to elevations in reward sensitivity and positive affect. Little is known, however, about how people with bipolar disorder respond to rewards and positive affect and how these tendencies relate to functioning or quality of life. Methods Persons diagnosed with bipolar I disorder and matched controls completed the Response to Positive Affect (RPA) measure and the Brief Quality of Life in Bipolar Disorder scale. Bipolar participants also completed the Reward Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 39 publications
4
53
0
2
Order By: Relevance
“…A central psychiatric component to BD the response to rewarding stimuli and tendency for rewarding life events to precipitate hypomanic or manic episodes (Edge et al, 2013;Gruber, 2011). The ventral striatum is a key component of neural circuitry underlying reward processing including the ventral prefrontal cortex and the anterior cingulated brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…A central psychiatric component to BD the response to rewarding stimuli and tendency for rewarding life events to precipitate hypomanic or manic episodes (Edge et al, 2013;Gruber, 2011). The ventral striatum is a key component of neural circuitry underlying reward processing including the ventral prefrontal cortex and the anterior cingulated brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical patients used more strategies to dampen positive affect and lower strategies to intensify positive emotions. This is in line with other studies that found that people with bipolar I disorder and depressed individuals reported more dampening responses to positive affect than did control participants (Edge et al, 2013;Werner-Seidler, Banks, Dunn, Moulds, 2013). Clinical population differed from nonclinical samples in the use of reappraisal (changing the way one thinks about potentially emotion-eliciting events) to regulate affective responses (Ray, McRae, Ochsner., & Gross, 2010) but not in their emotional expression (changing the way one behaviorally responds to emotion-eliciting events).…”
Section: Hierarchical Regression Analysessupporting
confidence: 89%
“…Moreover, people with bipolar disorder reported more dampening responses to positive affect than did control participants (Edge et al, 2013;Shapero et al, 2015). In community samples, results indicated that current and formerly depressed individuals engage in dampening strategies in response to positive affect (Nelis, Holmes, & Raes, 2015;Werner-Seidler, Banks, Dunn, & Moulds, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study of 43 participants with BDI found that goal-attainment events were associated with increased manic symptoms (Johnson et al, 2000), a finding which was later replicated in a larger sample (n ¼125) (Johnson et al, 2008). Individuals with BDI reported mania after achieving an important success and avoiding rewarding activities to prevent mania (Edge et al, 2013). This effect may be related to the regulation of the behavioural activation system, a motivational system which regulates reward-mediated behaviours and emotional homeostasis (Depue and Iacono, 1989).…”
Section: Goal-attainment Eventsmentioning
confidence: 97%